Human genetic and reproductive technologies - an international medico-legal-religious impasse? - Nordin, Musa Mohd (Bangladesh Journal of Medical Science, 2011)
DOI: 10.3329/bjms.v10i1.7311 Bangladesh Journal of Medical Science Vol.10 No.1 Jan 2010 pp.1-10